SCIENTIFIC BASICS AND PROSPECTS OF DEVELOPMENT OF PRODUCTION OF ORGANIC ANIMAL PRODUCTS IN RUSSIA - Anatoliy Alekseevich CHERNYAEV; Dmitriy Valerevich SERDOBINTSEV; Ekaterina Vladimirovna KUDRYASHOVA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The purpose of the study is to work out the scientific basics for the development of organic production livestock products for their application in the practice of the agro-industrial complex of Russia. In preparing the article, we took data from the Ministry of Agriculture of the Russian Federation, the Federal State Statistics Service of the Russian Federation, statistical materials FAOSTAT, EUROSTAT, scientific works of Russian and foreign scientists. The following methods of scientific research were used: statistical-economic, monographic, abstract-logical, calculation-constructive. Using the principles of a system approach, the scientific basics for the development of organic production, from the author’s point of view, has been developed, which is a form of scientific knowledge that studies the sequence of creation and development of enterprises in organic agriculture, ensuring the effective construction and interaction of the system structure. A system analysis of the environment in which the development of organic livestock production is supposed to take place has made it possible to divide the scientific basics into three blocks of elements (technological, economic and social), including all its stages (problem-tasks-solution).The probable efficiency of production of organic livestock products is substantiated on the basis of its total cost indicator, predicted before 2030, taking into account the use of organic production methods and without them, using extrapolation and analogy of European experience.